Population genetics of two endemic loach species, Iksookimia hugowolfeldi and I. longicorpa (Cypriniformes, Cobitidae), illuminate taxonomy, paleo-drainages, and river capture in the southern Korean Peninsula - Da-Song Choi; Hyo-Jin Kim; Myeong-Hun Ko; Ra-Yeon Myung; Yong-Jin Won (Zoosystematics and Evolution)
Pleistocene climatic fluctuations reshaped the East Asian coastline, facilitating the formation of extensive paleo-river networks that influenced freshwater biodiversity. Here, we examine how the formation of ancient river systems has influenced the population genetic structures of two sister species of freshwater loaches, Iksookimia hugowolfeldi and I. longicorpa, found in the southern Korean Peninsula. We conducted a multi-locus genetic analysis of an extensive sample of 208 individuals from 21 populations across their entire distribution range. According to a phylogenetic tree constructed using nuclear DNA, the two sister species diverged approximately 5.5 million years ago. However, there was a discrepancy between the taxonomic identification of I. hugowolfeldi populations and the phylogenetic result. A wrong species boundary between the two sister species previously assumed and a genetic signature of headwater river capture were found to explain the discrepancy. An overall radiative diversification of multiple allopatric genetic clusters in the sister species highlights the significant influence of geographic barriers in today’s isolated river systems. Simulations of ancient river connections, shaped by fluctuating sea levels, compellingly illustrate how localized reconnections through these historic networks during the ice ages have significantly shaped the population genetic structures of these sister species. The present study identifies the important role of paleo-river systems in facilitating the geographic connectivity of Iksookimia, which provides useful insights into the broader phylogeography of other riverine organisms in the Korean Peninsula and East Asia.